1995
DOI: 10.1080/00268979500100201
|View full text |Cite
|
Sign up to set email alerts
|

High resolution FTIR spectrum of vinyl fluoride near 9 μm: rovibrational analysis of the v 7 band

Abstract: The Fourier transform infrared spectrum of CH2--~-CHF has been investigated in the v7 band region around 115 5 cm -1 at a resolution of about 0"002 cm-1. This fundamental of symmetry species A' yields an a/b hybrid band with a prevalent contribution of the a-type component. The band is affected by first-order b-Coriolis resonance with the v9 + v12 combination, and the interactions are markedly stronger for the K'a = 11 and 12 levels; local perturbations with crossings due to higher-order a-and b-Coriolis reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The spectrum around 8.7 mm is characterized by the ro-vibrational absorptions belonging to the n 7 normal mode which corresponds to the CÀF stretching vibration. The spectral structure was originally assigned by Stoppa et al, [21] although the observed irregularities, ascribed to a/b-type Coriolis couplings with the neighbouring n 9 + n 12 vibrational state, were described only qualitatively. Herein, this perturbation, which mainly affects rovibrational states with K a !…”
Section: Modelling Of the Ro-vibrational Spectrummentioning
confidence: 98%
See 2 more Smart Citations
“…The spectrum around 8.7 mm is characterized by the ro-vibrational absorptions belonging to the n 7 normal mode which corresponds to the CÀF stretching vibration. The spectral structure was originally assigned by Stoppa et al, [21] although the observed irregularities, ascribed to a/b-type Coriolis couplings with the neighbouring n 9 + n 12 vibrational state, were described only qualitatively. Herein, this perturbation, which mainly affects rovibrational states with K a !…”
Section: Modelling Of the Ro-vibrational Spectrummentioning
confidence: 98%
“…Ground state [21] n 7 = 1 n 9 = n 12 = 1 showing the uneven line spacing caused by the Coriolis coupling of vibrational states n 7 = 1 and n 9 = n 12 = 1. Lower trace: FTIR spectrum; Upper trace: theoretical spectrum computed using the data of Table 1 and the obtained transition dipole moments.…”
Section: Self-broadening Collisions and Absorption Cross-sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Di culties in identifying the weak lines of the 37 Cl isotopomer in badly overlapped regions have been overcome by resorting to the spectra of pure monoisotopic 37 Cl species. This study is part of a more extensive investigation in our laboratory of the spectroscopic characteristics of di erent halogenated compounds [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…11 Ground-state constants were determined many years ago from microwave spectra 12,13 and more recently using microwave data available in the literature together with infrared combination differences coming from the ν 7 fundamental. 14 The present work deals with the interpretation of the rovibrational structure of the ν 8 , ν 10 , and ν 11 bands of vinyl fluoride in the region between 750 and 1050 cm -1 where highresolution spectra have been investigated for the first time. The determination of the spectroscopic parameters of these fundamentals are also of considerable interest, since the related absorptions fall in the range of atmospheric windows for the detection of trace gases.…”
Section: Introductionmentioning
confidence: 99%